Абсолютная суммируемость ряда Фурье по мультипликативной системе - Абиш С.Р.; Мади А.Қ.; Рымқұлова А.Р. (European Research Materials, 2026)
Абсолютная суммируемость ряда Фурье по мультипликативной системе